2021
DOI: 10.1021/acs.biochem.0c00892
|View full text |Cite
|
Sign up to set email alerts
|

A Dynamic Substrate is Required for MhuD-Catalyzed Degradation of Heme to Mycobilin

Abstract: The noncanonical heme oxygenase MhuD from Mycobacterium tuberculosis binds a heme substrate that adopts a dynamic equilibrium between planar and out-of-plane ruffled conformations. MhuD degrades this substrate to an unusual mycobilin product via successive monooxygenation and dioxygenation reactions. This article establishes a causal relationship between heme substrate dynamics and MhuD-catalyzed heme degradation, resulting in a refined enzymatic mechanism. UV/vis absorption (Abs) and electrospray ionization m… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 47 publications
(166 reference statements)
0
11
0
Order By: Relevance
“…It was previously shown that the major products of WT IsdG and WT MhuD are staphylobilin and mycobilin, respectively [13,17]. Recently, it was realized that a second-sphere variant of MhuD that decreases population of the "ruffled" conformation, W66F, changes the major product of MhuD from mycobilin to biliverdin [20]. The ESI-MS data reported here reveals that decreased population of the "ruffled" conformation of IsdG induced by the W67F substitution also increases production of biliverdin (Fig.…”
Section: Functional Role Of a Conserved Second-sphere Trp Residuementioning
confidence: 99%
See 2 more Smart Citations
“…It was previously shown that the major products of WT IsdG and WT MhuD are staphylobilin and mycobilin, respectively [13,17]. Recently, it was realized that a second-sphere variant of MhuD that decreases population of the "ruffled" conformation, W66F, changes the major product of MhuD from mycobilin to biliverdin [20]. The ESI-MS data reported here reveals that decreased population of the "ruffled" conformation of IsdG induced by the W67F substitution also increases production of biliverdin (Fig.…”
Section: Functional Role Of a Conserved Second-sphere Trp Residuementioning
confidence: 99%
“…It turns out that MhuD degrades heme to a third product, mycobilin [17], via sequential monooxygenation and dioxygenation steps [18]. Recently, it has been reported that both the R26S and W66F second-sphere substitutions can change the primary MhuD product from mycobilin to biliverdin [19,20]. These observations have been attributed to a mechanism where the structural and electronic dynamics of heme-bound MhuD are critical: MhuD converts "ruffled" heme to meso-hydroxyheme and "planar" meso-hydroxyheme to mycobilin.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It turns out that MhuD degrades heme to a third product, mycobilin [17], via sequential monooxygenation and dioxygenation steps [18]. Recently, it has been reported that both the R26S and W66F second-sphere substitutions can change the primary MhuD product from mycobilin to biliverdin [19,20]. These observations have been attributed to a mechanism where the structural and electronic dynamics of heme-bound MhuD are critical: MhuD converts "ruffled" heme to meso-hydroxyheme and "planar" meso-hydroxyheme to mycobilin.…”
Section: Introductionmentioning
confidence: 99%
“…A recently established UV/Vis absorption (Abs) spectroscopy-based assay was employed to quantify heme ruffling instead of the more laborious crystallography-based approach previously utilized for IsdI [1,3,5]. Rufflinginduced heme electronic structure changes have been invoked as a key component in non-canonical heme oxygenase mechanisms [10,14,16,18,20,21], so a careful assessment of the heme electronic structure of these variants using 1 H NMR and MCD spectroscopies was carried out. Finally, the rates of heme oxygenation by WT and W67F IsdG were quantified using a UV/Vis Absbased assay and the products of these enzyme variants were identified using electrospray ionization mass spectrometry (ESI-MS) [15].…”
Section: Introductionmentioning
confidence: 99%